A Systematic Literature Review (SLR) Study on Gamification as A Teaching Tool in Fourth Industrial Revolution (4IR) - Nor Zaitul Shahira Zakaria; Hanifah Mahat (Proceeding of International Conference on Multidisciplinary Research, 2024)
The education revolution 4.0 has brought momentous changes in the global education landscape by emphasizing the use of technology and changes in teaching strategies that are more efficient and in line with the world's technological modernization. In this context, gamification appears as a valuable tool in creating a more interesting and effective learning experience. Therefore, this study aims to look at the theme of the study and discussion about the issue of using gamification as a teaching tool in the Industrial Revolution 4.0 (IR4.0). This systematic literature review (SLR) study was conducted by using articles from 2019 to 2023 from three databases namely Researchgate, Scopus, and Science Direct. These articles have been collected and then researched to ensure that the selected articles meet the focus of the study. A total of 19 out of 82 articles were selected to be discussed in this study. Overall, the study shows that four themes can be classified regarding the themes of previous studies on the issue of gamification in education. The theme is 1) digital integration in education, 2) digital gamification as a teaching strategy, 3) digital gamification design in the teaching process, and 4) the need for digital gamification in the teaching process. Therefore, there is a need for a comprehensive study such as a study on the development of a gamification-based teaching model as a guide and in-depth reference for teachers, especially in the teaching and learning process. So, with that, the whole essence of this study will provide a comprehensive overview of the role of gamification in bringing education to a more relevant and viable direction, especially in the era of education 4.0.